Calling Planet Earth!!! Is anybody listening…? Sun Ra and Karlheinz Stockhausen as intergalactic collaborators - Lesser, Clare (Jazz Research Journal, 2022)
Travelling the space-ways, two figures. One from Saturn, one from Sirius: brought together in a speculative conversation that crosses space and time. A message to Earth: ‘Get your house in order!’ Sun Ra (1914–1993) wrote extensively throughout his life. Of his over 350 prose-poems, nearly half are directly concerned with exploring concepts of meta-reality, astro-Black identity, and lost time via the coming and consequences of ‘the cosmic age’. For Karlheinz Stockhausen (1928–2007), the ‘astro’ played out through the interpenetration of the micro and the macro in text and music. Interplanetary vibrations mingle with earthly micro-particles, the celestial and the fantastic combine in music’s transformative ability to bring profound change. Using a combination of Jacques Derrida’s (1930–2004) deconstructive technique of the animadversion, and the interview ‘cut-up’, as employed by Christian Marclay (b. 1955), this provocation will take the form of a ‘sampled cosmic conversation’ of Ra and Stockhausen’s own words.